Estruturações melódico-harmônicas nos 50 Ponteios de Camargo Guarnieri - Pereira, Gesiel Vilarubia [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The aim of this work is to study the 50 Piano Ponteios of Camargo Guarnieri, focusing on the analysis of their melodic and harmonic structures, seeking to understand the structural aspects of the composer's poetics in this cycle of pieces. We initially examine the transformations incurred by Guarnieri's melodic-harmonic writing in the period that this collection was composed, and a produce a historical-stylistic contextualization. This contextualization focuses on the Brazilan nationalism which was influenced by Brazilian philosopher and critic Mário de Andrade, and Guarnieri’s experiences with different harmonic languages. In preparation for the analysis, a textural classification of the 50 Ponteios is performed, as well as a verification of some formal consistencies within this collection. The dissertation is also directed to the examination of the choices of the materials present in the construction of the melodies and harmonies, and extends to the observation of the compositional procedures characteristic of Guarnieri – in other words, his poetics. From this analytical investigation we can observe, in the Ponteios and in other works by this composer, the recurrence of a melodic motif which we call The Guarnieri Motive. In terms of harmony, we are struck by the recurrence of a specific symmetrical harmonic structure, used as dominant function in cadential moments. We may also verify the care the composer took to use symmetrical structures in scalar, harmonic and formal contexts. Whenever possible, the analysis was permeated by dialogues established with researchers on Guarnieri’s work, and by the observation of the relationship between Guarnieri’s compositional decisions and his aesthetic opinion, as influenced directly by the book Ensaio sobre a música brasileira by Mário de Andrade.

Tendo como objeto de estudo os 50 Ponteios para piano de Camargo Guarnieri, este trabalho se concentra na análise de suas estruturações melódicas e harmônicas, almejando compreender aspectos estruturais da poética do compositor neste ciclo de peças. Apresenta-se, inicialmente, um diálogo entre as transformações sofridas pela escritura melódico-harmônica de Guarnieri durante o período de composição desta coleção e uma contextualização histórico-estilística, na qual são focalizadas, principalmente, suas buscas por um nacionalismo influenciado por Mário de Andrade e suas experiências com diferentes idiomas harmônicos. Propõe-se, ainda como texto preparatório para as análises, uma classificação textural dos 50 Ponteios e, ainda, a verificação de algumas constâncias formais dentro desta coleção. Nos capítulos seguintes, esta dissertação se direciona para a verificação das escolhas dos materiais presentes na construção das melodias e harmonias e se estende sobre observação dos procedimentos composicionais característicos de Guarnieri – sua poética. A partir desta investigação analítica, constatamos, nos Ponteios e em outras obras do compositor, a recorrência de um motivo melódico o qual denominamos Motivo Guarnieri. Na dimensão harmônica, chamou-nos a atenção a reincidência de uma determinada estrutura harmônica simétrica, utilizada com função Dominante nos momentos cadenciais, além do cuidado, por parte do compositor, em usar estruturas simétricas nos contextos escalares, harmônicos e formais. Sempre que possível, as análises foram permeadas por diálogos estabelecidos com pesquisadores da obra de Guarnieri e pela observação das relações entre suas decisões composicionais e seu posicionamento estético, diretamente influenciado pelo livro Ensaio sobre a música brasileira, de Mário de Andrade.
Melodic and harmonic structures in the 50 Ponteios of Camargo Guarnieri
Keywords: Melodic-harmonic analysis; Camargo Guarnieri; Ponteios; Análises melódico-harmônicas